Recurrent pregnancy loss: challenge to obstetricians - Shetty, Mamatha B.; Malyala, Mounica; Swarup, Asha; Pocha, Suneha; Pathadan, Davis Sabu; Raju, Ankush (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Recurrent pregnancies loss (RPL) is physically and emotionally devastating situation for the parents, along with difficult situation for obstetrician to handle. Present study aimed at investigation of the significance of various etiology in relation to pregnancy outcome in cases of recurrent pregnancy loss. Methods: It is a retrospective analysis of patients who presented to M. S. Ramaiah Medical college with recurrent miscarriage between April 2014 and August 2015. ANA was done on the basis of clinical and laboratory data which was obtained and eventually diagnosis was made. The study results were analysed in terms of term live births, maternal and fetal complications. Results: Out of the RPL cases that were studied, 78 patients came with recurrent pregnancy loss. Out of these cases, endocrine abnormalities, like diabetes mellitus and hypothyroidism were the maximum 26.92% and 12.82% respectively. Followed by unexplained causes were 37.3%. Thrombophila and APLA positive cases constituted for 16.66% and 3.4% respectively. ANA positive and cervical incompetence were 6.4% each. Conclusions: Recurrent pregnancy loss is very difficult situation to handle. Various etiology need various specialists, and requirements, and management mainly depends on the cause for recurrent pregnancy loss.